Informal institutions and cross-country income differences - Stephen Knowles; Clayton Weatherston (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2006)
There is a growing literature which analyses, using cross-country data, whether institutions or geography is the most important deep determinant of income per capita. The empirical proxies used for institutions in this literature, however, focus only on formal institutions, rather than informal institutions, despite the fact that North (1990) emphasised the importance of informal institutions. We include a measure of informal institutions, a concept we argue is closely related to social capital and cultural norms, in a representative deepdeterminants framework and find informal institutions to be just as important a deep determinant of income levels as are formal institutions.
Keywords: Z13; O11; 330; Institutions; deep determinants; social capital; culture